2020
DOI: 10.1016/j.avsg.2020.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Total Aortoiliac Revascularization for TASC-II C&D Lesion with Kissing Self-Expanding Covered Stents

Abstract: Background: The endovascular approach has been widely used for aortoiliac occlusive disease (AIOD), especially for aortic bifurcation and iliac artery Trans-Atlantic Inter-Society Consensus II (TASC-II) A and B lesions. However, the outcomes of self-expanding covered stents (SECSs) for extensive aortoiliac lesion remain unclear. This study aimed to assess the short-term patency of kissing covered stents for the revascularization of aortoiliac TASC-II C and D diseases. Methods: Thirty-three patients with TASC-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
10
0
5
Order By: Relevance
“…16 Kissing iliac stents are associated with acceptable patency rates, comparable in some cases with open surgery; however, no high quality randomised controlled trials comparing open vs. endovascular AIOD reconstructions are available. 17,18 Furthermore, a variety of novel endovascular therapeutic approaches have been reported for AIOD, involving the use of both covered and bare metal stents in the aorta or iliacs. The Covered vs.…”
Section: Discussionmentioning
confidence: 99%
“…16 Kissing iliac stents are associated with acceptable patency rates, comparable in some cases with open surgery; however, no high quality randomised controlled trials comparing open vs. endovascular AIOD reconstructions are available. 17,18 Furthermore, a variety of novel endovascular therapeutic approaches have been reported for AIOD, involving the use of both covered and bare metal stents in the aorta or iliacs. The Covered vs.…”
Section: Discussionmentioning
confidence: 99%
“…19 Studies reporting on the use of kissing stents have demonstrated acceptable mid-and long-term patency. 20,21 The Covered versus Balloon Expandable Stent Randomised Trial (COBEST) also showed acceptable patency rates in the context of AIOD and a benefit when a covered stent was used in TASC C and D lesions. 22,23 Further studies have shown that using covered iliac stents for TASC C and D lesions is associated with favorable technical success, hence this is becoming a common technique to address AIOD.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Further studies have shown that using covered iliac stents for TASC C and D lesions is associated with favorable technical success, hence this is becoming a common technique to address AIOD. [6][7][8]10,[21][22][23][24] When using kissing stents in severe AIOD, however, the positioning of the stents and the discrepancy between the stented lumen and the aortic lumen ("radial mismatch") can have a negative impact on patency. 7,10,22 The CERAB technique aims to minimize this radial mismatch and achieve a more "anatomical" distal aortic and iliac reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…We used a 14 mm balloon instead of a thrombectomy catheter and successfully removed the aortic-iliac artery thrombus. Considering that the patient had long aortic-bilateral iliac artery stenosis, we used CERAB [ 8 ], a technique with a high medium- and long-term patency rate in the reconstruction of complex AIOD [ 9 , 10 ]. After bilateral femoral artery angiography, the path map was made to determine the opening of the bilateral internal iliac artery, after which the bilateral common iliac artery stent was implanted into the lower segment of the abdominal aorta.…”
Section: Discussionmentioning
confidence: 99%